2002
DOI: 10.1291/hypres.25.927
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibitors Attenuate Increased Blood Pressure in Renovascular Hypertensive Models, but Not in Deoxycorticosterone-Salt Hypertension.

Abstract: COX-2 is an inducible cyclooxygenase (COX) that has been reported to be expressed in the macula densa and surrounding cortical thick ascending limb in normotensive rats. The present study assessed the contribution of COX-2 in three different rat models of hypertension, each characterized by a different activation of the renal renin-angiotensin system. Mean blood pressure (MBP) in the rat 2 kidney-1 clip (2K1C) model was significantly reduced with a COX-2 selective inhibitor, NS-398 (10 mg/kg, p.o., twice a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…This is consistent with our previous results showing that TTA has no effect on BP in spontaneously hypertensive rats that have low plasma renin concentration, as well as with earlier studies showing that renin gene expression and COX2 expression have a parallel expression in the rat cortex in renal hypertension (21). However, COX2 inhibition has been found to lower BP in renovascular hypertension in 2K1C rats (33) and in rats with aortic coarctation (56), which is contrary to our results, while others have found no effect of COX2 inhibition on BP (41). These differences must for the time being be attributed to differences in models and strains but may also indicate COX2-independent effects of some of the inhibitors used.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our previous results showing that TTA has no effect on BP in spontaneously hypertensive rats that have low plasma renin concentration, as well as with earlier studies showing that renin gene expression and COX2 expression have a parallel expression in the rat cortex in renal hypertension (21). However, COX2 inhibition has been found to lower BP in renovascular hypertension in 2K1C rats (33) and in rats with aortic coarctation (56), which is contrary to our results, while others have found no effect of COX2 inhibition on BP (41). These differences must for the time being be attributed to differences in models and strains but may also indicate COX2-independent effects of some of the inhibitors used.…”
Section: Discussionsupporting
confidence: 93%
“…As shown previously (19,24,27), we found that COX2 activity was enhanced in the clipped kidney and, to some extent, also in the nonclipped kidney of untreated rats (33). In contrast, COX1 expression was unchanged in both kidneys of 2K1C, and the activity compared with total COX activity was reduced in proportion to the increase in COX2 activity.…”
Section: Discussionsupporting
confidence: 87%
“…COX-1 is abundant in the kidneys, while COX-2 is minimally expressed at specific time points during development, in hypertension, and at sites of inflammation. We reported previously that COX-2 was induced in kidneys and plays a significant role in the development of 2K1C and 1K1C renovascular hypertension [17]. In separate experiments, we also reported that during acute and chronic inflammation [18,19], COX-2 was induced by pathological stimulation and was observed in macrophages and fibroblasts that accumulated in the UUO kidneys.…”
Section: Discussionmentioning
confidence: 53%
“…COX2 selective inhibitors were expected to act as a 'super aspirin' that would not exert the adverse effects typical of classical NSAIDs (DeWitt 1999, Majima et al 2003. However, in some organs such as kidneys, COX2 is expressed constitutively (Okumura et al 2002) and is necessary for the kidney to mature after birth (Norwood et al 2000), suggesting that even 'super aspirin' can cause adverse effects. Thus, selective activation of EP3 receptor signaling may be a more promising treatment than COX2 inhibition.…”
mentioning
confidence: 99%